Factors Affecting The Implementation of Green Procurement: Empirical Evidence from Indonesian Educational Institution - Ilyas Masudin; Bangalie Summah; Fien Zulfikarijah; Dian Palupi Restuputri (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2020)
This paper reported the factors affecting the adoption of green procurement in Indonesian educational institutions. A quantitative method is used to understand the effects between variables on green procurement implementation. Data from respondents working on the divisions of procurement from higher degree institutions in the province of East Java Indonesia are collected in this study. The results were indicated that there are no significant effects on middle management staff, awareness, and corporate responsibility on the implementation of green procurement on educational institutions. At the same time, there is a significant impact of green supply approaches such as ISO certification and eco-design product strategy on the adoption of green procurement.